The suicides among the Romanian police and public safety personnel in the period 2016-2021 - Bogdan MÎNJINĂ (Studia Universitatis Babes-Bolyai, 2024)
There is an important concern of public and professional organizations in the police and public safety sector to identify the best practices for suicide risk management, especially in USA. The suicide phenomenon from 2016 to 2021 at the level of the Ministry of Internal Affairs of Romania , captured through the annual suicide rates, varied positively or negatively compared with the annual suicide rates from Romania and with those at the level of institutions with a similar activity profile from the international level, from the USA and Italy. Based on the socio-demographic data available, the self-murderers' profiles at the level of MIA were created, but in their use, the particular aspects of the suicidal phenomenon must be considered. The self-murderers from the Romanian police and public safety institutions used firearms in 45.7% of the cases during the analyzed period. The algorithm used to predict the annual suicide numbers in the period 2022-2025 at the MIA level revealed that they will follow an increasing trend. In the period 2016-2021, the annual number of suicides among Romanian police and public safety personnel was higher than the number of deaths among the same personnel caused by accidents during service and assaults.